1995
DOI: 10.2165/00002018-199512030-00006
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatraemia and the Syndrome of Inappropriate Antidiuretic Hormone Secretion (SIADH) Induced by Psychotropic Drugs

Abstract: The use of psychotropic drugs has been associated with the syndrome of inappropriate antidiuretic hormone secretion (SIADH) in a number of case reports. SIADH is characterised by the sustained release of antidiuretic hormone (ADH) from the posterior pituitary. The patients have a reduced ability to excrete diluted urine, ingested fluid is retained, and the extracellular fluid expands and becomes hypo-osmolar. The cardinal signs are hyponatraemia, serum hypoosmolality and a less than maximally diluted urine. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
69
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 98 publications
0
69
0
4
Order By: Relevance
“…And other research fi ndings [17] suggested a considerable association between TCA and the occurrence of hyponatremia. Th e results of some recent studies [18] showed a lower incidence of hyponatremia in the application of TCAs (0.01% -0.33%) in comparison with previous studies (16.7%) [19,20], that can be explained by diff erent methodological approaches (active monitoring, higher hyponatremia threshold).…”
Section: Discussionmentioning
confidence: 78%
“…And other research fi ndings [17] suggested a considerable association between TCA and the occurrence of hyponatremia. Th e results of some recent studies [18] showed a lower incidence of hyponatremia in the application of TCAs (0.01% -0.33%) in comparison with previous studies (16.7%) [19,20], that can be explained by diff erent methodological approaches (active monitoring, higher hyponatremia threshold).…”
Section: Discussionmentioning
confidence: 78%
“…In our patient, the hyponatraemia was probably associated with the sertraline use. Its occurrence at 9 days after the antidepressant treatment was initiated (other authors have reported that hyponatraemia occurred after a median of 13 days of SSRI use, 5 together with the return of normal sodium plasma levels after the SSRI had been discontinued, reinforces the causality hypotheses. In addition, the advanced age of the patient might have favoured the antidepressant-induced SIADH by increasing antidiuretic hormone secretion and the response to osmolar stimuli.…”
mentioning
confidence: 62%
“…SIaDH is a well-recognized complication of many psychotropic drugs [7]. also, there are a few reports of benzodiazepine like lorazepam induced hyponatremia in literature [8].…”
Section: Discussionmentioning
confidence: 99%